2017
DOI: 10.1016/j.bbamem.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides are degraded by the cytosolic proteases of human erythrocytes

Abstract: Well-studied and promising antimicrobial peptides (AMPs), with potent bactericidal activity, in vitro, have yet to have a significant impact in human medicine beyond topical applications. We previously showed that interactions of AMPs with concentrated human erythrocytes inhibit many of them, and suggested that screens and assays should be done in their presence to mimic host cell inhibition. Here, we use AMPs to characterize the activity of proteases that are associated with human erythrocytes. The representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 49 publications
1
70
1
Order By: Relevance
“…These two sequences, which belong to distinct families (35), both have potent, sterilizing antimicrobial activity in standard laboratory assays (38) against a range of gram-negative and gram-positive bacteria, including drug-resistant strains (35). However, like many known AMPs, ARVA and NATT are strongly inhibited by host cells (23), are susceptible to proteolysis (22), have poor solubility, and are somewhat cytotoxic (35).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two sequences, which belong to distinct families (35), both have potent, sterilizing antimicrobial activity in standard laboratory assays (38) against a range of gram-negative and gram-positive bacteria, including drug-resistant strains (35). However, like many known AMPs, ARVA and NATT are strongly inhibited by host cells (23), are susceptible to proteolysis (22), have poor solubility, and are somewhat cytotoxic (35).…”
Section: Resultsmentioning
confidence: 99%
“…With a few exceptions, discovery of new AMPs has been achieved by the trial-and-error modification of known sequences. Even then, the major impediments to therapeutic applications discussed here, one or more of which likely apply to most known AMPs (22,23), are not usually assessed until after the peptide design/discovery phase. This approach reduces opportunities for feedback and down-selection of AMPs that have impediments, ultimately limiting the flow of promising new AMP candidates into the drug development pipeline.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Selectivity for bacteria over mammalian cells is attributed to the reduced anionic character of the mammalian cell membrane and its rigidity due to the presence of cholesterol . While some AMPs display potent cell lysis, they generally suffer from reduced activity in serum containing physiological fluids due to protease degradation and protein binding . To combat these drawbacks, recent efforts have been made toward synthesizing AMP mimics comprised of proteolytic‐resistant backbones.…”
Section: Methodsmentioning
confidence: 99%
“…AMPs have amphipathic features that mirror phospholipids, thus allowing them to interact with and exploit vulnerabilities inherent in essential microbial structures such as cell membranes (3). Until now, the antibacterial activity of more than 1000 peptides from different eukaryotic and prokaryotic sources have been investigated to find a suitable antimicrobial alternative for antibiotics (4,5). It has been demonstrated that venom of snakes, scorpions and spiders has strong antibacterial effects (6).…”
Section: Introductionmentioning
confidence: 99%